Graft Engineering and Adoptive Immunotherapy: New Approaches to Promote Immune Tolerance After Hematopoietic Stem Cell Transplantation - Bertaina, Alice; Roncarolo, Maria Grazia (Frontiers in Immunology, 2019)
Allogeneic hematopoietic stem cell transplantation (HSCT) is a curative therapeutic option for a wide range of immune and hematologic malignant and non-malignant disorders. Once transplanted, allogeneic cells have to support myeloid repopulation and immunological reconstitution, but also need to become tolerant to the host via central or peripheral mechanisms to achieve the desired therapeutic effect. Peripheral tolerance after allogeneic HSCT may be achieved by several mechanisms, though blocking alloreactivity to the host human leukocyte antigens while preserving immune responses to pathogens and tumor antigens remains a challenge. Recently uncovered evidence regarding the mechanisms of post-HSCT immune reconstitution and tolerance in transplanted patients has allowed for the development of novel cell-based therapeutic approaches. These therapies are aimed at inducing long-term peripheral tolerance and reducing the risk of graft-versus-host disease (GvHD), while sparing the graft-versus-leukemia (GvL) effect. Thus, ensuring effective long term remission. Today, haploidentical stem cell transplants have become a widely used treatment for patients with hematological malignancies. A myriad of ex vivo and in vivo T-cell depletion strategies have been adopted, with the goal of preventing GvHD while preserving GvL in the context of immunogenetic disparity.  T-cell/CD19 B-cell depletion techniques, in particular, have gained significant momentum, because of the high rate of leukemia-free survival and the low risk of severe GvHD. Despite progress, improved treatments are still needed in a portion of patients to further reduce the incidence of relapse and achieve long-term tolerance. Current post-HSCT cell therapy approaches designed to induce tolerance and minimizing GvHD occurrence include the use of i)  T cells, ii) regulatory Type 1 T (Tr1) cells and iii) engineered FOXP3+ regulatory T cells. Future protocols may include post-HSCT infusion of allogeneic effector or regulatory T cells engineered with a chimeric antigen receptor (CAR). In the present review, we describe the most recent advances in graft engineering and post-HSCT adoptive immunotherapy.